Alfalfa Production in Florida - Carrol G. Chambliss (EDIS)
Alfalfa is a high-quality legume forage crop that is mainly used for hay or silage but can be green chopped or grazed in some situations. It can be utilized by horses, dairy, and beef cattle. There is a great demand for alfalfa hay by the Florida horse and dairy industries. Thousands of tons of alfalfa hay are shipped into Florida each year. Thus, occasionally there is interest in growing alfalfa in the state. This document is SS-AGR-188, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2003.